1968
DOI: 10.1161/01.cir.38.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Origin of the Left Coronary Artery from the Pulmonary Artery

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…11,13,14 This disorder may go undetected until a previously well adult experiences cardiac failure, chest pain, effort syncope, or sudden death. 5,7,15 Two-dimensional echocardiography plays an important role in the diagnosis of the anomalous left coronary artery from the pulmonary trunk by establishing the normal origins of the left and right coronaries coming off the aortic sinuses. It can also identify the site of entry of an anomalous left coronary artery into the pulmonary trunk.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14 This disorder may go undetected until a previously well adult experiences cardiac failure, chest pain, effort syncope, or sudden death. 5,7,15 Two-dimensional echocardiography plays an important role in the diagnosis of the anomalous left coronary artery from the pulmonary trunk by establishing the normal origins of the left and right coronaries coming off the aortic sinuses. It can also identify the site of entry of an anomalous left coronary artery into the pulmonary trunk.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction Flamm et al [1968] observed the anomalous origin of a left coronary artery from the pulmonary artery. Smith [1950] described a single coronary artery in a review.…”
mentioning
confidence: 99%